Suivi physiologique et entraînement en hypoxie chez des joueurs de tennis élite - Brechbuhl, C. (University of Lausanne, 2018)
When playing tennis by high level players, the performance limits are of technical, tactical, psychological and / or physiological origin, with reciprocal implications. Based on an analysis of the activity combined with technological changes, we are aiming the development of new methods to improve performance capacity. The purpose of this work is to design and valid a new field test in order to determine the effectiveness of a new training technique. We first validated the reliability of a new ball machine technology, before using it to validate a new tennis-specific stress test. The analysis of the data obtained lead to determine key points linked to the expression of the resources of men and women at elite level: a) in male players, we observe an impact of the fatigue on the technical alteration, b) in female, the transition junior - professional circuit is marked by a higher aerobic potential and a more efficient backhand, especially in ball speed. Then, we realized that after a cycle of repeated sprints in hypoxia (RSH), Greater improvement in physical and parameters was observed after only 5 sessions of RSH vs. RSN in tennis players. With a low hypoxic dose RSH improved total time to exhaustion and time to the second ventilatory threshold in a tennis-specific aerobic test. Repeated-sprint training in hypoxia could provide an effective strategy as compared with similar training in normoxia to improve performance and to delay technical impairments near exhaustion in tennis players. After checking the RSH advantage for tennis players, we have changed the method by including ball strokes. The validity of these new training techniques opens up new possibilities for adapting the principles of polarized tennis training, with applications related to the use of the ball machine and/or stress test data, as well as a very demanding training design in hypoxia. Thus, we can better combine tactical-technical development with other "pillars" of performance. These new methods open the way for a potentially more effective practice on the level of performance, as more fundamental aspects such as prophylaxis by streamlining the training method